The Role of Digital Financial Inclusion in Improving Payment System Efficiency in Developing Countries - Ferdiansyah, Rudi; Ridzki, Mohamad Maulana (Economics Monetary Journal, 2025)
Digital financial inclusion has become one of the important strategies in improving the efficiency of payment systems, especially in developing countries. With increasingly widespread access to digital financial services such as mobile money, e-wallets, and digital payment apps, developing countries have great potential to expand access to financial services and reduce dependence on cash. This study aims to analyze the role of digital financial inclusion in improving the efficiency of payment systems in developing countries. The method used is multiple linear regression analysis, which examines the relationship between digital financial inclusion and payment efficiency through variables such as the percentage of users of digital financial services, people's access to these services, and the number of electronic transactions per capita. The results show that digital financial inclusion has a significant influence on improving payment efficiency, characterized by a decrease in transaction costs and shorter time in the payment process. In addition, it was found that digital infrastructure and digital financial literacy are still challenges that need to be overcome to achieve optimal financial inclusion benefits. This research contributes as suggestion for government policies and investments in digital infrastructure are essential to maximize the role of digital financial inclusion in payment systems